Two Nineteenth-Century Copies of Joseph Prémare's Notitia linguæ sinicæ. (10th March 2022) - Kua, Paul
Abstract: French Jesuit Joseph Prémare, a missionary to Qing Dynasty China, had completed by the end of 1728 the draft of a book entitled Notitia linguæ sinicæ, intended to assist aspiring Catholic missionaries from Europe in learning the Chinese language. One of the original manuscripts sent from Canton to Paris, now held in the Bibliothæque nationale de France in Paris, was rediscovered in the 1810s by the French sinologist Jean-Pierre Abel-Rémusat, and became the source for some manuscript copies, made mostly before the work's eventual publication in 1831. This paper examines two of these manuscript copies dated between 1825 and 1830, held respectively in the Archive of the School of Oriental and African Studies in London and the the Bayerische Staatsbibliothek in Munich, both important in their own ways, and both somewhat misunderstood and largely neglected by recent studies.